Method for preparing high-purity uranium carbide microspheres through microfluidic-assisted internal gel process

Through microfluidic assisted internal gel process and carbon thermal reduction reaction, the problem of low phase purity in the prior art was solved, and UC nuclear fuel microspheres with uniform size and high purity were prepared.

CN119430935AActive Publication Date: 2025-02-14TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202411467081.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-14
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

When preparing UC nuclear fuel microspheres in the existing internal gel process, the uranium gel liquid has poor room temperature stability, uneven gel microsphere size, and low phase purity of UC microspheres, making it difficult to prepare UC microspheres with uniform size and pure phase.

Method used

Using microfluidic assisted internal gel process, monodispersed gel microspheres were prepared through a microfluidic device, and combined with carbon heat reduction reaction, the sintering system was optimized to improve the phase purity of UC microspheres.

Benefits of technology

Long-term stability of uranium gel liquid at room temperature and rapid gelation at high temperatures were achieved, and UC nuclear fuel microspheres with uniform size and high purity were prepared, solving the problem of low phase purity of UC microspheres.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430935A_ABST
    Figure CN119430935A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-purity uranium carbide microspheres by a microfluidic-assisted internal gelation process, which comprises the following steps of: designing a uranium glue solution component containing carbon black to obtain a uranium glue solution which is stable for a long time at room temperature and quickly gelates at high temperature; the preparation method comprises the following steps: preparing gel microspheres with uniform size by using a uranium glue solution as a micro-fluidic dispersion phase through a micro-fluidic assisted inner gel process; the pore structure in the gel microspheres is maintained through washing and soaking with propylene glycol monomethyl ether, so that the crack-free gel microspheres are obtained; the UC nuclear fuel microspheres which are uniform in size, good in sphericity degree and high in phase purity are prepared through the carbon thermal reduction reaction of the non-cracking gel microspheres under the optimized sintering schedule, and development of ultrahigh-temperature gas cooled reactor nuclear fuel is expected to be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nuclear fuel preparation, and in particular to a method for preparing high-purity uranium carbide microspheres using a microfluidic-assisted internal gel process. Background Art

[0002] my country's fourth-generation nuclear power technology ultra-high temperature gas-cooled reactor requires uranium carbide (UC) nuclear fuel microspheres with high thermal conductivity and high uranium density. The internal gel process can avoid direct handling of radioactive powders, ensure the safety of experimenters, and can evenly dope carbon black to reduce the temperature and time of carbon thermal reduction reaction. It is currently the mainstream preparation method for UC microspheres. However, in the internal gel process for preparing UC nuclear fuel microspheres, the uranium colloid containing carbon black has poor room temperature stability, the gel microspheres are uneven in size, and the phase purity of the UC microspheres is low. It is difficult to prepare pure phase UC microspheres, and the final product often contains unreacted UO2, UC2 or carbon black. Therefore, it is urgent to optimize the internal gel process to prepare UC microspheres with uniform size and pure phase. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0004] To this end, the embodiment of the present invention proposes a method for preparing high-purity uranium carbide microspheres by a microfluidic-assisted internal gel process. The present invention solves the technical problems of poor room temperature stability of uranium colloid containing carbon black, uneven size of gel microspheres, and low phase purity of UC microspheres, and prepares UC microspheres with uniform size and high purity.

[0005] The present invention proposes a method for preparing high-purity uranium carbide microspheres by a microfluidic-assisted internal gel process, comprising the following steps:

[0006] (a) preparing uranium colloid;

[0007] (b) using the uranium colloid as a dispersed phase, preparing monodisperse gel microspheres through a microfluidic device;

[0008] (c) the gel microspheres are sequentially aged, washed, and dried to obtain dry microspheres;

[0009] (d) sintering the dried microspheres to obtain high-purity microspheres.

[0010] In some embodiments, the uranium colloid solution is prepared by mixing a HMUR solution containing carbon black with a uranyl nitrate solution in a volume ratio of 1.2 to 1.4 to obtain a uranium colloid solution containing carbon black, wherein the concentration of the uranyl nitrate solution is 2.6 to 2.8 mol / L, and the acidity is n(NO3 - / U) is 1.8-1.9, the HMUR solution containing carbon black is obtained by dispersing carbon black into the HMUR solution, the HMUR solution is a mixed solution of hexamethylenetetramine and urea, the concentration of the hexamethylenetetramine is 2.5-2.8 mol / L, and the concentration of urea is 3.5-5 mol / L.

[0011] In some embodiments, the uranium colloid containing carbon black has n(Urea / UO2 2+ ) is 2~2.3, n(HMTA / UO2 2 + ) is 1.10~1.30, n(C / UO2 2+ ) is 1 to 5.

[0012] In some embodiments, the uranium colloid containing carbon black is stable at room temperature for more than 85 minutes and forms gel microspheres within 6 to 7 seconds at 70° C. to 90° C.

[0013] In some embodiments, dispersing the carbon black into the HMUR solution is dispersing the carbon black into the HMUR solution under the conditions of ultrasonic power of 100-200 W, ultrasonic time of 60-180 min, and dispersant.

[0014] In some embodiments, in step (b), dimethyl silicone oil is used as a continuous phase, and the continuous phase squeezes or shears the dispersed phase in the microfluidic device to obtain monodisperse sol droplets, and the sol droplets fall into dimethyl silicone oil at 70°C to 90°C and solidify into monodisperse gel microspheres.

[0015] In some embodiments, the gel microspheres in step (c) are aged by placing them in dimethyl silicone oil at 70° C. to 90° C. for 1 to 5 minutes.

[0016] In some embodiments, the gel microspheres in step (c) are washed by sequentially using vinyl chloride, 0.5-1 mol / L ammonia water, and propylene glycol methyl ether for 4-6 times, with each washing time being 20-30 minutes.

[0017] In some embodiments, the drying of the gel microspheres in step (c) is performed by soaking the washed gel microspheres in propylene glycol methyl ether, and drying them in a far-infrared drying oven at 60° C. to 80° C. for 12 to 36 hours while soaking.

[0018] In some embodiments, the dried microspheres are sintered in an argon atmosphere, and the dried microspheres are first heated to 200°C to 240°C at a rate of 0.5 to 2°C / min and kept warm for 200 to 360 min; then heated to 460 to 480°C at a rate of 0.5 to 2°C / min for 30 to 60 min; then heated to 1000°C to 1100°C at a rate of 3 to 5°C / min and kept warm for 60 to 200 min to convert UO3 into UO2; then heated to 1500°C to 1550°C at a rate of 3 to 5°C / min and kept warm for 200 to 360 min to convert UO2 into UC; finally heated to 1700°C to 1750°C at a rate of 3 to 5°C / min and kept warm for 200 to 400 min to fully densify the UC phase.

[0019] Compared with the prior art, the beneficial effects of the present invention are:

[0020] The present invention introduces microfluidics to assist the internal gelation process, and combines the carbon thermal reduction reaction to solve the technical problems of poor room temperature stability of uranium colloid containing carbon black, uneven size of gel microspheres, and low phase purity of UC microspheres. The UC nuclear fuel microspheres prepared by the present invention are expected to promote the development of ultra-high temperature gas-cooled reactor nuclear fuel.

[0021] The invention obtains uranium colloid which is stable for a long time at room temperature and quickly gelled at high temperature by designing uranium colloid components containing carbon black; uses uranium colloid as a dispersed phase of microfluidics, and prepares gel microspheres with uniform size by a microfluidics-assisted internal gelation process; maintains the pore structure in the gel microspheres by washing and soaking with propylene glycol methyl ether, thereby obtaining gel microspheres without cracks; and the gel microspheres without cracks undergo a carbothermal reduction reaction under an optimized sintering system to prepare UC nuclear fuel microspheres with uniform size, good sphericity and high phase purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0023] Figure 1 This is a flow chart of the method for preparing high-purity uranium carbide microspheres by the microfluidic-assisted internal gel process of the present invention;

[0024] Figure 2 The schematic diagram of the structure of preparing monodisperse gel microspheres by using a microfluidic device in the present invention;

[0025] Figure 3 This is a morphology image of the dried microspheres prepared in Example 1 of the present invention;

[0026] Figure 4 This is the overall morphology of the ceramic microspheres prepared in Example 1 of the present invention;

[0027] Figure 5The element distribution diagram of the cross section of the ceramic microsphere prepared in Example 1 of the present invention;

[0028] Figure 6 This is the XRD pattern of ceramic microspheres prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0030] The following describes a method for preparing high-purity uranium carbide microspheres by a microfluidic-assisted internal gel process according to an embodiment of the present invention with reference to the accompanying drawings.

[0031] like Figure 1 As shown, the method for preparing high-purity uranium carbide microspheres by microfluidic-assisted internal gel process of the present invention comprises the following steps:

[0032] (a) preparing uranium colloid;

[0033] (b) Using uranium colloid as the dispersed phase, monodisperse gel microspheres were prepared by microfluidic device;

[0034] (c) the gel microspheres are sequentially aged, washed, and dried to obtain dry microspheres;

[0035] (d) Sintering and drying the microspheres to obtain high purity microspheres.

[0036] In step (a), the uranium colloid solution is prepared by mixing the HMUR solution containing carbon black with the uranyl nitrate solution in a volume ratio of 1.2 to 1.4 to obtain the uranium colloid solution containing carbon black.

[0037] The concentration of uranyl nitrate solution is 2.6-2.8 mol / L, and the acidity is n(NO3 - / U) is 1.8-1.9. The HMUR solution containing carbon black is obtained by dispersing carbon black into the HMUR solution. The HMUR solution is a mixed solution of hexamethylenetetramine and urea. The concentration of hexamethylenetetramine is 2.5-2.8 mol / L and the concentration of urea is 3.5-5 mol / L. 2+ ) is 2~2.3, n(HMTA / UO2 2+ ) is 1.10~1.30, n(C / UO2 2+ ) is 1 to 5.

[0038] Based on a large number of experimental studies, it is found that the stability of uranium colloid containing carbon black is related to the lack of acidity and the urea content. The present invention obtains a uranium colloid that is stable for a long time at room temperature and quickly gels at high temperature by regulating the components of the uranium colloid containing carbon black.

[0039] The uranium colloid containing carbon black obtained by the invention is stable at room temperature for more than 85 minutes, and quickly forms gel microspheres within 6 to 7 seconds at 70 to 90 degrees Celsius, thus meeting the requirement of long-term stability of the uranium colloid at room temperature.

[0040] The specific process of dispersing carbon black into the HMUR solution is to disperse carbon black into the HMUR solution under the conditions of ultrasonic power of 100-200W, ultrasonic time of 60-180min, and dispersant to obtain a HMUR solution in which nano-scale carbon black is uniformly dispersed. The dispersant is 1-10wt% of Digo 760W dispersant. It is understood that the dispersant can also be other suitable types.

[0041] In step (b), the monodisperse gel microspheres are prepared by using a microfluidic device using uranium colloid as the dispersed phase, specifically, as follows: Figure 2 As shown, the microfluidic device is a coaxial capillary microfluidic device, an aqueous uranyl nitrate solution and a HMUR solution containing carbon black are mixed in a magnetic bead micromixer to form a uranyl colloid solution that is stable for a long time at room temperature, the uranyl colloid solution is used as the dispersed phase of the microfluidic device, dimethyl silicone oil is used as the continuous phase of the microfluidic device, the continuous phase is squeezed or sheared in the microfluidic device to obtain monodisperse sol droplets, and the monodisperse sol droplets fall into dimethyl silicone oil at 70°C to 90°C and are quickly solidified into monodisperse gel microspheres.

[0042] In step (c), the gel microspheres are aged by placing them in dimethyl silicone oil at 70° C. to 90° C. for 1 to 5 minutes, thereby obtaining gel microspheres without uranium segregation; the gel microspheres are washed by sequentially using vinyl chloride, 0.5 to 1 mol / L ammonia water, and propylene glycol methyl ether for 4 to 6 times, with each washing time being 20 to 30 minutes; and the gel microspheres are dried by soaking the washed gel microspheres in propylene glycol methyl ether, and drying them in a far-infrared drying oven at 60° C. to 80° C. for 12 to 36 hours, thereby obtaining dry microspheres without cracks and rich in gel pore structure.

[0043] In step (d), the dried microspheres are sintered to obtain high-purity microspheres as follows: in an argon atmosphere, the dried microspheres are first heated to 200°C to 240°C at a rate of 0.5 to 2°C / min and kept warm for 200 to 360 minutes; then heated to 460 to 480°C at a rate of 0.5 to 2°C / min for 30 to 60 minutes; then heated to 1000°C to 1100°C at a rate of 3 to 5°C / min and kept warm for 60 to 200 minutes to convert UO3 into UO2; then heated to 1500°C to 1550°C at a rate of 3 to 5°C / min and kept warm for 200 to 360 minutes to convert UO2 into UC; finally heated to 1700°C to 1750°C at a rate of 3 to 5°C / min and kept warm for 200 to 400 minutes to fully densify the UC phase.

[0044] The UC microspheres prepared by the method of the invention have uniform size, good sphericity and a UC phase purity of up to 90-95wt%.

[0045] The method of the present invention is applicable to most carbide materials prepared by sol-gel process, and can be used to prepare zirconium carbide, aluminum carbide, tungsten carbide, uranium carbon oxide (UCO) and other materials by adaptive adjustment of the method of the present invention.

[0046] In addition, the present invention can not only be used for the preparation of carbide ceramic microspheres, but also can be used for the preparation of non-oxide microspheres, such as nitride microspheres, silicide microspheres, etc., by adding a carbon source, a nitrogen source or a silicon source to the inner gel solution.

[0047] Example 1

[0048] 0.81 g of carbon black was dispersed into 12.25 mL of HMUR solution under the conditions of 180 W ultrasonic power, 60 min ultrasonic time and 6 wt% of Digo 760W dispersant. The HMUR solution is a mixed solution of hexamethylenetetramine and urea, the concentration of hexamethylenetetramine is 2.64 mol / L, and the concentration of urea is 4.4 mol / L.

[0049] 10mL of 2.7mol / L, low acidity n(NO3 - The uranyl nitrate solution with a concentration of uranyl nitrate / UO2 = 1.85 was mixed with 12.25 mL of HMUR solution containing carbon black to obtain a uranium gel containing carbon black that was stable at room temperature for 85 min and solidified for 7 s at 80 °C. 2+ ) is maintained at 2, n(HMTA / UO2 2+ ) is maintained at 1.20, n(C / UO2 2+ ) remains at 2.5.

[0050] Using uranium colloid as the dispersed phase and dimethyl silicone oil as the continuous phase, monodisperse gel microspheres were prepared by a coaxial capillary microfluidic device. The gel microspheres were aged in dimethyl silicone oil at 80°C for 2 minutes, and then immediately taken out for a trichloroethylene-ammonia water-propylene glycol methyl ether combined washing process. Specifically, the gel microspheres were first washed with trichloroethylene 4 times, each time for 25 minutes, and then washed with 0.5 mol / L ammonia water 4 times, each time for 25 minutes, and finally washed with propylene glycol methyl ether 4 times, each time for 25 minutes. The washed gel microspheres were immersed in propylene glycol methyl ether and sent to a far-infrared oven at 60°C for drying for 30 hours to obtain dry microspheres without cracks, such as Figure 3 shown.

[0051] The dried microspheres were heated to 200°C at 0.5°C / min in an argon atmosphere and kept at 200°C for 360 min; then heated to 460°C at 0.5°C / min and kept at 460°C for 30 min; then the gel microspheres were heated to 1000°C at 3°C / min and kept at 1000°C for 120 min to convert UO3 into UO2; then heated to 1500°C at 3°C / min and kept at 1500°C for 240 min to convert UO2 into UC; finally, heated to 1700°C at 3°C / min and kept at 1700°C for 300 min to completely densify the UC phase and obtain high-purity UC ceramic microspheres, such as Figure 4 shown.

[0052] The cross section of the UC ceramic microsphere is scanned by energy spectrum line, such as Figure 5 As shown in the figure, it can be seen that carbon and uranium are evenly distributed, and there is no obvious segregation of uranium. The UC ceramic microspheres were subjected to XRD test, as shown in the figure. Figure 6 As shown, it can be seen that 92.9wt% of the ceramic microspheres prepared in the present invention are UC phase.

[0053] Example 2

[0054] 0.99g of carbon black was dispersed into 13mL of HMUR solution under the conditions of 180W ultrasonic power, 120min ultrasonic time and 6wt% of Digo 760W dispersant. The HMUR solution is a mixed solution of hexamethylenetetramine and urea, the concentration of hexamethylenetetramine is 2.7mol / L, and the concentration of urea is 4.5mol / L.

[0055] 10mL of 2.75mol / L, low acidity n(NO3 - The uranyl nitrate solution with a concentration of uranyl nitrate / UO2 = 1.88 was mixed with 13 mL of HMUR solution containing carbon black to obtain a uranium gel containing carbon black that was stable at room temperature for 90 min and solidified at 90 °C for 6 s. 2+) was maintained at 2.13, n(HMTA / UO2 2+ ) is maintained at 1.28, n(C / UO2 2+ ) is maintained at 3.

[0056] With uranium colloid as the dispersed phase and dimethyl silicone oil as the continuous phase, monodispersed gel microspheres were prepared by a coaxial capillary microfluidic device. The gel microspheres were aged in dimethyl silicone oil at 90°C for 1 min, and then immediately taken out for a trichloroethylene-ammonia-propylene glycol methyl ether combined washing process, specifically, the gel microspheres were first washed with trichloroethylene for 6 times, each time for 20 min, then washed with 1 mol / L ammonia for 6 times, each time for 20 min, and finally washed with propylene glycol methyl ether for 6 times, each time for 20 min. The washed gel microspheres were placed in propylene glycol methyl ether and soaked, and then sent to a far-infrared oven at 80°C for 15 h to obtain dry microspheres without cracks.

[0057] The dried microspheres were heated to 240°C at 0.5°C / min under an argon atmosphere and kept at 240°C for 250 min; then, the temperature was increased to 480°C at 0.5°C / min and kept at 480°C for 40 min; then, the gel microspheres were heated to 1100°C at 3°C / min and kept at 1100°C for 120 min to convert UO3 into UO2; then, the temperature was increased to 1550°C at 3°C / min and kept at 1500°C for 240 min to convert UO2 into UC; finally, the temperature was increased to 1750°C at 3°C / min and kept at 1750°C for 300 min to obtain high-purity UC microspheres.

[0058] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0059] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0060] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing high-purity uranium carbide microspheres by microfluidic-assisted internal gel process, characterized in that: The following steps are involved: (a) preparing uranium colloid; (b) using the uranium colloid as a dispersed phase, preparing monodisperse gel microspheres through a microfluidic device; (c) the gel microspheres are sequentially aged, washed, and dried to obtain dry microspheres; (d) sintering the dried microspheres to obtain high-purity microspheres.

2. The method according to claim 1, characterized in that The preparation of uranium colloid solution is to mix the HMUR solution containing carbon black with the uranyl nitrate solution with a volume ratio of 1.2 to 1.4 to obtain the uranium colloid solution containing carbon black, wherein the concentration of the uranyl nitrate solution is 2.6 to 2.8 mol / L, the acidity n(NO3 - / U) is 1.8-1.9, the HMUR solution containing carbon black is obtained by dispersing carbon black into the HMUR solution, the HMUR solution is a mixed solution of hexamethylenetetramine and urea, the concentration of the hexamethylenetetramine is 2.5-2.8 mol / L, and the concentration of urea is 3.5-5 mol / L.

3. The method according to claim 2, characterized in that The uranium colloid containing carbon black has n(Urea / UO2 2+ ) is 2~2.3, n(HMTA / UO2 2+ ) is 1.10~1.30, n(C / UO2 2+ ) is 1 to 5.

4. The method according to claim 3, characterized in that The uranium colloid containing carbon black is stable at room temperature for more than 85 minutes and forms gel microspheres within 6 to 7 seconds at 70 to 90 degrees Celsius.

5. The method according to claim 2, characterized in that The dispersing of carbon black into the HMUR solution is to disperse the carbon black into the HMUR solution under the conditions of ultrasonic power of 100 to 200 W, ultrasonic time of 60 to 180 min, and dispersant.

6. The method according to claim 1, characterized in that In the step (b), dimethyl silicone oil is used as a continuous phase, and the continuous phase squeezes or shears the dispersed phase in the microfluidic device to obtain monodisperse sol droplets, and the sol droplets fall into dimethyl silicone oil at 70° C. to 90° C. and solidify into monodisperse gel microspheres.

7. The method according to claim 1, characterized in that In the step (c), the gel microspheres are aged by placing them in dimethyl silicone oil at 70° C. to 90° C. for 1 to 5 minutes.

8. The method according to claim 1, characterized in that In the step (c), the gel microspheres are washed by using vinyl chloride, 0.5-1 mol / L ammonia water, and propylene glycol methyl ether in sequence for 4-6 times, with each washing time being 20-30 minutes.

9. The method according to claim 1, characterized in that In the step (c), the gel microspheres are dried by soaking the washed gel microspheres in propylene glycol methyl ether, and drying them in a far-infrared drying oven at 60° C. to 80° C. for 12 to 36 hours while soaking.

10. The method according to claim 1, characterized in that In the step (d), the dried microspheres are sintered in an argon atmosphere. The dried microspheres are first heated to 200°C to 240°C at a rate of 0.5 to 2°C / min and kept warm for 200 to 360 minutes; then heated to 460 to 480°C at a rate of 0.5 to 2°C / min for 30 to 60 minutes; then heated to 1000°C to 1100°C at a rate of 3 to 5°C / min and kept warm for 60 to 200 minutes to convert UO3 into UO2; then heated to 1500°C to 1550°C at a rate of 3 to 5°C / min and kept warm for 200 to 360 minutes to convert UO2 into UC; finally heated to 1700°C to 1750°C at a rate of 3 to 5°C / min and kept warm for 200 to 400 minutes to fully densify the UC phase.

Citation Information

Patent Citations

  • Internal gelation method for ceramic microspheres capable of keeping gel solution steady at normal temperature

    CN104671797A

  • Nuclear fuel micro ball prepared by full gelatinizing method

    CN1062126A

  • Uranium carbide nuclear fuel microspheres and preparation method thereof

    CN107910084A

  • Method for preparing uranium dioxide microspheres at normal temperature

    CN111039326A

  • Method for preparing monodisperse uranium dioxide microspheres

    CN111243770A

Cited By

  • Preparation method of hollow multilayer nuclear fuel microspheres

    CN121583596A

  • Carbon-doped gel ball taking hydro-thermally treated organic sugar as carbon source and preparation method of carbon-doped gel ball

    CN121648837A

  • Carbon-doped gel balls using hydrothermally treated organic sugar as carbon source and preparation method thereof

    CN121648837B